Mortality and morbidity in wild Taiwanese pangolin (Manis pentadactyla pentadactyla) - Sun, Nick Ching-Min; Arora, Bharti; Lin, Jing-Shiun; Lin, Wen-Chi; Chi, Meng-Jou; Chen, Chen-Chih; Pei, Curtis Jai-Chyi (PLOS ONE, 2019)
Globally, pangolins are threatened by poaching and illegal trade. Taiwan presents a contrary situation, where the wild pangolin population has stabilized and even begun to increase in the last two decades. This paper illustrates the factors responsible for causing mortality and morbidity in the wild Taiwanese pangolin (Manis pentadactyla pentadactyla) based on radio-tracking data of wild pangolins and records of sick or injured pangolins admitted to a Taiwanese wildlife rehabilitation center. Despite being proficient burrowers, results from radio-tracking show that Taiwanese pangolins are highly susceptible to getting trapped in tree hollows or ground burrows. Data from Pingtung Rescue Center for Endangered Wild Animals showed that trauma (73.0%) was the major reason for morbidity in the Taiwanese pangolin with trauma from gin traps being the leading cause (77.8%), especially during the dry season, followed by tail injuries caused by dog attacks (20.4%). Despite these threats, Taiwan has had substantial success in rehabilitating and releasing injured pangolins, primarily due to the close collaboration of Taiwanese wildlife rehabilitation centers over the last twenty years.